Sanitation potpourri: Criteria for planning mix of sanitation systems for citywide inclusive sanitation. (October 2022) - Mitra, Anant; Narayan, Abishek S; Lüthi, Christoph
Sanitation is a universal need and thus requires universal access. Despite having the world's largest sanitation campaign, only 37% of urban India has access to safely managed sanitation systems. Due to the heterogeneity of Indian cities, a mix of different sanitation systems is required to meet the demands of these rapidly urbanising cities. The Manila principles on Citywide Inclusive Sanitation (CWIS) propose a mix of technologies as a key pillar in achieving the Sustainable Development Goals on urban sanitation. However, there is a lack of understanding on the criteria to consider when planning the technological options for CWIS. The mega-city of Chennai is chosen as a case study, and mixed methods including a Faecal Waste Flow diagram (SFD), Social Network Analysis (SNA) and interviews are applied. This study then presents a set of 14 contextually relevant criteria for the implementation of sewered and non-sewered technologies in the city. The SFD shows that 35% of Chennai's faecal waste remains unsafely managed while using SNA identified that the water and sanitation utility, the municipal corporation and the slum clearance board are the best placed stakeholders in the city to create a change in the sanitation situation. Furthermore, 17 drivers and barriers for the implementation of non-sewered technologies are identified. The criteria catalogue was also theoretically tested for an example ward in Chennai. The findings of the study show that a catalogue of physical, technical, institutional and financial criteria is useful for planning a mix of technologies with the CWIS approach.